ANALYSIS OF FACTORS AFFECTING LABOR ABSORPTION IN THE TAPAL KUDA REGION OF EAST JAVA - Rachmaniyah, Bunga Ayufi; Wijaya, Riko Setya; Perdana, Putra (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
The research examines how labor absorption in East Java's Horseshoe region is influenced by several key factors: population, average years of schooling, TPAK, minimum wage, and GRDP per capita. Using panel data regression analysis through the Fixed Effect Model (FEM), determined by Chow and Hausman testing, the investigation adopts a quantitative methodology. The analysis draws on secondary data spanning 2014-2023, sourced from the Central Bureau of Statistics of the corresponding region. The results show that the variables of Total Population and TPAK have a positive and significant effect on employment. Meanwhile, the variables of Average Years of Schooling, Minimum Wage, and GRDP Per Capita have no significant effect, and even tend to be negative. This finding indicates that an increase in the active working-age population contributes to labor absorption, while formal education and wage policies have not been able to optimally encourage labor absorption in the region's dominant informal sector. This study provides policy implications for local governments in encouraging inclusive and quality-based employment growth.Keywords: Labor Absorption, Population, Average Years of Schooling, TPAK, Minimum Wage, GRDP Per Capita.